ASSESSMENT OF THE KNOWLEDGE ON PRE CONCEPTION CARE AMONG WOMEN OF REPRODUCTIVE AGE IN RUIRU SUB-COUNTY, KIAMBU COUNTY, KENYA - Joyce, Chepngetich; Keraka,Prof. Margaret; Njagi, Dr. Joan (Global Journal of Health Sciences, 2018)
Purpose: The study aimed at determining the knowledge on pre conception care among women of reproductive age in Ruiru Sub-County, Kiambu County. Materials and methods: Descriptive cross-sectional study design was used with a target population of 65,045 women of reproductive age, para one and above in Ruiru sub-county. Simple random sampling method was used to select study participants. A total of 384 women of reproductive age took part in the study. A semi-structured interviewer-administered questionnaire was used to collect data and Focused Discussion groups. Quantitative data from the questionnaire was checked daily for completeness and coded for appropriate computer entry. Thematic content analysis was done for Qualitative data from the FGDs and triangulated during discussion. Thereafter, data was analyzed using SPSS version 20.0 statistical package. Univariate and bivariate data analysis were involved. Chi-square was used to determine the significance of associations between variables. Data finding were then presented using tables, pie charts and bar graphs. Results: There is low level of knowledge on preconception care services among the study participants with a larger proportion who have never heard about the services and not able to name the components of preconception care and the main source of information was obtained from the health workers in the hospitals. Recommendations: Health education of women of reproductive age on preconception care services, its components and importance in the health facilities and institutions of higher learning so that they can have the knowledge on preconception care services hence increasing its utilization. This is because the utilization of preconception care services is influenced by the level of education, occupation and age. Keywords: Utilization, para, preconception care, woman of reproductive age